Supervisi Akademik Kepala Sekolah dalam Meningkatkan Profesional Guru di SMA Negeri 1 Blang Pidie - Jalisal Efendi, Murniati AR, Bahrun (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2016)
Academic supervision conducted by the principal is one of the factors affecting the increase in the quality of education in schools. To realize the improvement of the quality of education, the principal requires good planning in developing supervision programs to improve the professionalism of teachers. The purpose of this study was a) to determine the ability of the principal in planning supervision, a) strategy principals carry out supervision, c) policy principals in following up the results of supervision, d) the factors supporting and inhibiting supervision, and e) the achievement of academic supervision that conducted by the principal. This research uses descriptive method with qualitative approach. Data was collected through interviews, observation, and documentation. The subjects were teachers at SMAN 1 Blang Pidie, Aceh Barat Daya. The results showed: (1) Planning supervision carried out by the school principal has been running optimally, the principal who made planning supervision. (2) technical-tiknik implementation of academic supervision carried out by the school head has been systematically and have a plan so that teachers feel their support of principals in improving the quality of learning. (3) Follow-up of the supervision is done by noting the deficiencies in the current classroom observation, calling the teacher personally, and discuss the results with the teacher council meeting. (4) The inhibiting factors include the competence of the academic supervision head of the lower school, while the other supporting factors principals and teachers have the commitment, motivation, and a sense of family that performs implementation of academic supervision already achieved effectively despite some shortcomings in carrying out academic supervision is very assist teachers in improving and increasing the quality of teaching.